An exploratory data analysis of COVID-19 impacts on education - Paritala, Venu (International Journal of Scientific Reports, 2024)
The global spread of COVID-19 has significantly impacted in education, leading to the widespread adoption of online learning as face-to-face interactions in schools, colleges, and universities diminished. This article employs an exploratory data analysis (EDA) approach to develop a statistical model that comprehensively assesses the influence of COVID-19 on the world’s education system until December 2021. The research delves into the complexities of this impact, examining day-to-day and week-to-week variations in education globally. It also compares the educational effects in different nations, with a specific focus on contrasting India with neighbouring countries and those severely affected by the pandemic. The study analyses immediate effects and addresses implications for the healthcare sector, offering insights for planning in the event of future outbreaks. By exploring data and trends, the article aims to provide valuable insights into the multifaceted impact of COVID-19 on global education, facilitating informed decision-making in the face of unprecedented challenges.